2018
DOI: 10.1002/admi.201701147
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient PVDF‐HFP/Colloidal Alumina Composite Separator for High‐Temperature Lithium‐Ion Batteries

Abstract: Toward high‐temperature lithium‐ion batteries, adding inorganic materials are proposed as an effective strategy. However, inorganic particles tend to aggregate in the polymer matrix, causing degradation in battery performance. Here, a PVDF‐HFP/colloidal Al2O3 composite separator is prepared with a phase inverse method. The colloidal Al2O3 particles well dispersed in the PVDF‐HFP polymer matrix substantially enhance the mechanical strength of the PVDF‐HFP separator. The PVDF‐HFP/colloidal Al2O3 composite separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 32 publications
0
77
0
Order By: Relevance
“…The LFP/Li batteries based on PVDF‐HFP/colloidal‐TiO 2 separator deliver remarkable discharge capacity at elevated temperatures, as given in Figure e,f. Similarly, Ali et al reported the same concept as reported by Waqas et al of using colloidal oxide as a filler with PVDF‐HFP to ensure the uniformity but they used bisolvent dissolution method for fabrication of PVDF‐HFP/colloidal Al 2 O 3 composite separator. The use of two different solvents increases the porosity with a uniform microporous structure due to the variation in evaporation rate of solvents, as shown in Figure g.…”
Section: Types Of Separatorsmentioning
confidence: 81%
See 3 more Smart Citations
“…The LFP/Li batteries based on PVDF‐HFP/colloidal‐TiO 2 separator deliver remarkable discharge capacity at elevated temperatures, as given in Figure e,f. Similarly, Ali et al reported the same concept as reported by Waqas et al of using colloidal oxide as a filler with PVDF‐HFP to ensure the uniformity but they used bisolvent dissolution method for fabrication of PVDF‐HFP/colloidal Al 2 O 3 composite separator. The use of two different solvents increases the porosity with a uniform microporous structure due to the variation in evaporation rate of solvents, as shown in Figure g.…”
Section: Types Of Separatorsmentioning
confidence: 81%
“…However, for high electrochemical performances, the separator should be thin with high porosity for efficient transport of lithium‐ions. Therefore, for increasing the mechanical strength, the thickness of separator must be increased, while by increasing the thickness of separator, the ionic conductivity and lithium‐ion transference number decrease, which effects the electrochemical performances . Therefore, on a practical level, the separator should own appropriate properties in order to achieve high electrochemical performances and ensure the safety as well.…”
Section: Separator Characterization and Requirementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkable achievements have been achieved to address these issues involved in Li metal anodes, including exploiting electrolyte additives to construct stable SEI films, designing high‐modulus solid/composite electrolytes to impede dendrite penetration, and engineering stable artificial interfacial layers to inhibit dendrite growth . However, the relatively infinite volume change induced by the hostless feature of Li plating/stripping at a high areal capacity is a formidable challenge.…”
mentioning
confidence: 99%